Jenis Dan Distribusi Lumba - Lumba Di Perairan Teluk Kiluan Lampung - Stany R Siahainenia; Isnaniah ' (Ilmu Perairan (Aquatic Science), 2010)
About one-third of dolphin species in the world is living in Indonesia,including some other types categorized by rareness and threatened of extinct. Thepurposes of this research are to analyse visually the dolphin behaviour on thesurface of water area at its real habitat. Equipments used in this research wereidentification book of dolphin, and visual sensus on dolphin with line transec zigzagmethod. In Kiluan Bay, there were two species of dolphin found, namely Stenellalongirostris (Spinner dolphin) and Tursiops truncatus (Bottlenose dolphin). Duringperception, the coastal water were predominated by Spinner dolphin, 61,33%.Dolphin movement in coastal water of Kiluan Bay between 100 to 800 metres.Keywords: Stenella longirostris, Bottlenose dolphin, Kiluan Bay